Expresiones decimales no peridicas y nmeros irracionales - Valdivieso Rodriguez, Julio Milder (2019)
The learning session aims to obtain information on the non-periodic decimals and irrational numbers of students in the second grade of Secondary Education of the educational institution "San Nicols", by analyzing the information provided using a video. To obtain the information, the originality, flexibility and fluency shown in the examples were examined and for the mathematical capacities the examples proposed were examined, as well as the logical coherence between information and requirements. As a result of the analysis conducted, we conclude that students show high levels of flexibility, fluency and clarity when understanding exercises by elaboration; that the originality is not very high due to the tendency to imitate the worked examples; that students reveal greater capacity for understanding when they know the context and dominate the mathematical environment; and that group work is more fruitful than individual work.